National income analysis - Schultze, Charles L. (Englewood Cliffs, N.J. : Prentice-Hall, 1971)
A clear, brief introduction to modern national income analysis, introduces the study of economics as a whole, and the role of national income analysis (macroeconomic) in economics.
Bibliography: p. 155-156.
osa; 20/09/18
Loans
Keywords: Gross national product; Gross national product; National income